Impact of muscle strength on knee joint stability in static loading - Li, Ping-yue; Yin, Qing-shui; Hang, Hua-yang; Li, Jian-yi; Shen, Hong-yuan; Wang, Ze-jin; Wang, Qing (Nan fang yi ke da xue xue bao = Journal of Southern Medical University, 2010)
To study the in vivo stability of normal and anterior cruciate ligament (ACL)-injured knee joint before and after epidural anesthesia under 134 N pre-loading and evaluate the influence of muscular tension on the knee stability. Eight volunteers with unilateral ACL rupture and normal contralateral knee were enrolled in this study. CT (3D) images and 2 orthogonal images of the knee were captured at 0°, 30°, 60°, and 90° under 134 N pre-loading. The orthogonal images were used to recreate the in vivo knee positions at each of the targeted flexion angles by 2D/3D registration to analyze the tibial translation data. The anterior tibia translation of both the intact and ACL-injured knees after anesthesia was significantly different from that before anesthesia at all the angles (P<0.05). The anterior tibial translation of the intact knee after anesthesia increased by 1.7 mm at 0°, 2.7 mm at 30°, 2.6 mm at 60°, and 2.3 mm at 90°, as compare to the increase of ACL-injured knee by 4.2 mm, 2.6 mm, 1.2 mm, and 1.6 mm, re